33.9k views
1 vote
Help me Please please help me help me

Help me Please please help me help me-example-1

2 Answers

5 votes

Answer:y=-4 x=1.

Explanation:

User Elver Loho
by
5.9k points
3 votes

Answer:

• Let the equation be :


→ \: { \boxed{ \tt{y = mx + b}}}

• when x is 0, y is -6. So let's substitute:


→ \: { \tt{ - 6 = (m * 0) + b}} \\ \\ → \: { \tt{b = - 6}}

• Therefore, equation becomes;


→ \: { \boxed{ \tt{y = mx - 6}}}

• when x is 1, y is -10. So let's substitute:


→ \: { \tt{ - 10 = (m * 1) - 6}} \\ \\ → \: { \tt{ - 10 = m - 6}} \\ \\→ \: { \tt{m = - 4}}

• Therefore final relation becomes:


→ \: { \boxed{ \boxed{ \bf{y = - 4x - 6}}}}

User DinoMyte
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.